2016
DOI: 10.1016/j.cgh.2016.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Model to Predict Transplant-free Survival of Patients With Acute Liver Failure

Abstract: Background & Aims: Patients with acute liver failure (ALF) have a high risk of death that can be substantially reduced with liver transplantation. It is a challenge to predict which patients with ALF will survive without liver transplant because available prognostic scoring systems are inadequate. We devised a mathematical model, using a large dataset collected by the Acute Liver Failure Study Group (ALFSG),that can predict transplant-free survival in patients with ALF. Methods: We performed a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(119 citation statements)
references
References 24 publications
2
113
1
3
Order By: Relevance
“…The Model for End‐Stage Liver Disease (MELD) is defined as 10 × [0.957 × log(4) + 0.378 × log(bilirubin) + 1.12 × log(INR)] for dialyzed patients and 10 × [0.957 × log(creatinine) + 0.378 × log (bilirubin) + 1.12 × log(INR)] for patients not dialyzed . The ALFSG prognostic index calculates the log odds (logit) for 21‐day transplant‐free survival as 2.67 – 0.95(HE*) + 1.56(etiology*) – 1.25(vasopressor use*) – 0.70(ln bilirubin) – 1.35(ln INR) . For low coma grade use HE insert 0; for high coma grade use insert 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Model for End‐Stage Liver Disease (MELD) is defined as 10 × [0.957 × log(4) + 0.378 × log(bilirubin) + 1.12 × log(INR)] for dialyzed patients and 10 × [0.957 × log(creatinine) + 0.378 × log (bilirubin) + 1.12 × log(INR)] for patients not dialyzed . The ALFSG prognostic index calculates the log odds (logit) for 21‐day transplant‐free survival as 2.67 – 0.95(HE*) + 1.56(etiology*) – 1.25(vasopressor use*) – 0.70(ln bilirubin) – 1.35(ln INR) . For low coma grade use HE insert 0; for high coma grade use insert 1.…”
Section: Methodsmentioning
confidence: 99%
“…The most widely used prognostic criteria in APAP‐ALF patients are the King's College criteria (KCC) . While initially published in 1989, subsequent studies that have used KCC have shown relatively poor sensitivity of the APAP criteria, ranging 25%‐76% . More recently, the Acute Liver Failure Study Group (ALFSG) prognostic index also demonstrated limited sensitivity (41%) in APAP‐ALF …”
mentioning
confidence: 99%
“…However, this study was limited to a small number of patients. More recently, the new ALFSG prognostic index derived from patients with ALF of varying etiologies was developed . This model predicted 21‐day transplant‐free survival with a c‐statistic of 0.84 using five clinical variables (hepatic encephalopathy grade, etiology of ALF, vasopressor use, bilirubin, and INR).…”
Section: Discussionmentioning
confidence: 99%
“…For predicting outcomes, the King’s College criteria (KCC) for nonparacetamol‐related ALF, the U.S. Acute Liver Failure Study Group (ALFSG) index for fulminant HAV infection (HAV‐ALFSG), the new ALFSG prognostic index published in 2016, the United Network for Organ Sharing–modified Model for End‐Stage Liver Disease (MELD), and MELD including sodium (MELD‐Na) scores according to Organ Procurement and Transplantation Network guidelines were assessed at the time of diagnosis of ALF …”
Section: Methodsmentioning
confidence: 99%
“…Commonly used criteria evaluate multiorgan impairment (encephalopathy and metabolic acidosis), etiology, and severity of coagulopathy as the most important factors for listing ALF patients. King's College criteria 41 are the most commonly applied; however, other algorithms have been proposed over time 42, 43 . Nevertheless, several factors, such as recipient age, severity of pre-transplant illness, comorbidities, and the nature of graft used, could affect the outcome of emergency LT 38 .…”
Section: Timing To Liver Transplantationmentioning
confidence: 99%